Rationalize properly with steps
1/√3-√2-1 . please urgent
Answers
Answer:
Step-by-step explanation:
Hello friends!!
Here is your answer :
\frac{1}{ \sqrt{3} - \sqrt{2} - 1}
= \frac{1}{( \sqrt{3} - \sqrt{2} ) - 1} \times \frac{ ( \sqrt{3} - \sqrt{2} ) + 1 }{ (\sqrt{3} - \sqrt{2} ) + 1}
= \frac{ (\sqrt{3} - \sqrt{2} ) + 1}{(( \sqrt{3} - \sqrt{2} ) - 1)( \sqrt{3} - \sqrt{2} ) + 1)}
= \frac{ (\sqrt{3} - \sqrt{2} ) + 1}{ {( \sqrt{3} - \sqrt{2} ) }^{2} - {(1)}^{2} }
= \frac{ \sqrt{3} - \sqrt{2} + 1 }{3 + 2 - 2 \sqrt{6} - 1}
= \frac{ \sqrt{3} - \sqrt{2} + 1}{4 - 2 \sqrt{6} }
Now, rationalise this denominator..
= \frac{ \sqrt{3} - \sqrt{2} + 1}{4 - 2 \sqrt{6} } \times \frac{4 + 2 \sqrt{6} }{4 + 2 \sqrt{6} }
= \frac{( \sqrt{3} - \sqrt{2} + 1)(4 + 2 \sqrt{6}) }{(4 - 2 \sqrt{6})(4 + 2 \sqrt{6} ) }
= \frac{ 4 \sqrt{3} - 4 \sqrt{2} + 4 + 2 \sqrt{18} - 2 \sqrt{12} + 2 \sqrt{6} }{16 -24 }
\frac{4 \sqrt{3} - 4 \sqrt{2} + 4 + 18 \sqrt{2} - 4 \sqrt{3} + 2 \sqrt{6} }{ - 8}
= \frac{14 \sqrt{2} + 2 \sqrt{6} + 4 }{ - 8}
Hope it helps you... ☺️☺️☺️☺️
# Be Brainly
i dono its time to sleep